ERYTHROCYTE COUNT, HEMOGLOBIN LEVEL, AND MEAN CORPUSCULAR HEMOGLOBIN OF EID AL-ADHA SACRIFICIAL GOATS IN MUSHOLLA AL-IKHWAN PATIH NAMBI DENPASAR CITY - Vebyola Alben Kamase; Siswanto; Nyoman Sadra Dharmawan (Buletin Veteriner Udayana, 2025)
Goats are among the earliest domesticated livestock, playing a significant role in human life, including as a source of protein and as sacrificial animals in religious rituals. The objective of this research is to ascertain erythrocyte count, haemoglobin level, and MCH of sacrificial goats in Musholla Al-Ikhwan Patih Nambi, Denpasar City. The research method employed was observational, with a purposive sampling technique. The sample size was 19 male goats that were slaughtered on Eid al-Adha day and were clinically healthy. The parameters observed included erythrocyte count (RBC), haemoglobin (Hb), and MCH. The instrument used to analyse blood samples is the Veterinary Haematology Analyzer Licare CC 3200Vet. The results indicated an average RBC 11.26x106/uL, haemoglobin 9.63g/dL, and MCH 8.51pg. The study's findings indicate that goats deemed to be in good health and slaughtered during Eid al-Adha at Musholla Al-Ikhwan Patih Nambi Denpasar City exhibited normal haematological parameters.